2012
DOI: 10.1021/es302245r
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in Soil Inhibits Mercury Uptake and Translocation in Rice (Oryza sativa L.)

Abstract: A great number of studies have confirmed that mercury-selenium (Hg-Se) antagonism is a widespread phenomenon in microorganisms, fish, poultry, humans, and other mammals. However, by comparison, little attention has been paid to plants. To investigate the influence of Se on the uptake and translocation of methylHg/inorganic Hg (MeHg/IHg) in the rice-soil system, we determined the levels of Se, IHg, and MeHg in different parts of rice plants (including the root, stem, leaf, husk, and grain (brown rice)) and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(77 citation statements)
references
References 46 publications
4
72
0
1
Order By: Relevance
“…An inverse relationship between Hg species and Se was previously observed in rice grain (e.g., Zhang et al, 2012) as well as fish tissue (Peterson et al, 2009), while the trend was inverse but weak for this data set (p>0.05, Table 4). In rice grain, an inverse relationship between Hg species and Se may reflect competition for thiols in phloem.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…An inverse relationship between Hg species and Se was previously observed in rice grain (e.g., Zhang et al, 2012) as well as fish tissue (Peterson et al, 2009), while the trend was inverse but weak for this data set (p>0.05, Table 4). In rice grain, an inverse relationship between Hg species and Se may reflect competition for thiols in phloem.…”
Section: Resultssupporting
confidence: 60%
“…This is a retrospective study of archived rice germplasm, and other matrices (e.g., paddy soil or irrigation water) were not available. Other researchers reported a strong positive correlation between rice THg and MeHg concentrations for rice cultivated in China, California, USA and Cambodia (Rothenberg et al, 2014), while an inverse correlation was observed between rice Hg species and Se (Zhang et al, 2012). We hypothesize interactions will be similar among these Madagascar rice varieties.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For Hg T analysis, soil samples were digested in a water bath (95°C) using concentrated HCl and HNO 3 (1:3, v/v; Meng et al 2010;Zhang et al 2012). Concentrations of Hg T in the digestion or extraction solutions were measured using a DMA-80 direct mercury analyzer (Milestone, Italy) based on EPA Method 7473.…”
Section: Methodsmentioning
confidence: 99%
“…One possibility is to reduce the uptake of Hg by plants as well to reduce the bioavailability of Hg in plants to consumers. In the last decades several studies showed the antagonistic action of Se in soil on the uptake and translocation of Hg in plants (Shanker et al, 1996a,b;Thangavel et al, 1999;Mounicou et al, 2006;Zhang et al, 2012). Mercury has a high affinity to bind with Se and form insoluble mercury selenides, whichcan prevent negative effects of mercury in animals (rev in Raymond et al 2004).…”
Section: Introductionmentioning
confidence: 99%